Efektifitas Sayur Pepaya Muda dan Sayur Daun Kelor terhadap Produksi ASI pada Ibu Post Partum Primipara - Warjidin Aliyanto; Rosmadewi Rosmadewi (Politeknik Kesehatan Tanjung Karang, 2019)
Mother's milk (ASI) have a role a very important role in the baby's growth process that starts from the beginning of its birth, so it is expected that breast milk production in postpartum mothers can meet the needs of babies at the beginning of their lives. The problem in this study was that 54% of primipara postpartum mothers had not yet produced breast milk on day 3 or 4. According to Istiqomah et al (2014), Zakaria's research (2016), the papaya fruit and Moringa leaf act as Laktogogum which can increase milk production and facilitate breast milk expenditure. This study aims to determine the effectiveness of consumption of young papaya vegetables and Moringa leaf vegetables on breast milk production in postpartum primipara mothers in the independent practice of midwives in Bandar Lampung City in 2018. The indicators used to determine breast milk production are seen from baby weight gain at 30 days first life. This type of research is quantitative research using the Quasi-experimental design, namely Non-Equivalent Control Group Design. The subjects of the study were 90 primiparous postpartum mothers. Data collection uses primary data. Analysis using the Independent Sample T-Test. The results showed increased breast milk production in primipara postpartum mothers who consumed young papaya vegetables seen from the average increase in baby weight at 30 days at 930 grams and primipara postpartum mothers who consumed kelor leaf vegetables on average baby weight gain 1270 gram. Whereas in primipara postpartum mothers who did not consume young papaya and kelor leaf vegetables, the average increase in body weight of infants aged 30 days were 847 grams. There was a significant difference in breast milk production in primiparous postpartum mothers between those who consumed young papaya vegetables and Moringa leaf vegetables to increase infant weight at 30 days with p-value 0.001. As for effectiveness, consumption of vegetable Moringa leaves is more effective at increasing the baby's weight at 30 days of age compared to consuming young papaya vegetables.